Estimating the Economic Loss Due to Vibriosis in Net-Cage Cultured Asian Seabass (Lates calcarifer): Evidence From the East Coast of Peninsular Malaysia - Mohd Yazid, Siti Hajar; Mohd Daud, Hassan; Azmai, Mohammad Noor Amal; Mohamad, Nurliyana; Mohd Nor, Norhariani (Frontiers in Veterinary Science, 2021)
This study aims to estimate the economic loss due to vibriosis in the production of Asian seabass in floating net-cages on the East coast of Peninsular Malaysia. Asian seabass has contributed significantly to Malaysia’s economic activities and food security. However, its production can be hindered by the occurrence of diseases, such as vibriosis, causing severe economic losses to farmers. A questionnaire-based survey was conducted on 14 small-scale monoculture Asian seabass net-cage farms. Using a stochastic bioeconomic model and inputs from the survey, existing literature, and expert opinion, the economic losses were determined. Moreover, this model considered the prevalence of Vibrio spp. at a farm on the east coast and the risk posed by its infection from hatcheries. The results showed that 71.09% of Asian seabass simulated in the stochastic model survived. The mortality rate due to vibriosis and other causes was at 16.23% and 12.68%, respectively. The risk posed by Vibrio spp. infection from hatcheries contributed to 2.77% of the increase in Asian seabass mortality. The stochastic model estimated that the total cost of producing a tail of Asian seabass was €2.69 per kg. The economic loss of vibriosis was estimated at €0.19 per tail per kg, which represents 7.06% of the total production cost of Asian seabass per kg. An increase in the prevalence of clinical vibriosis and vibriosis case fatality rate at 42% and 100%, respectively, will lead to an increase in the cost of grow-out Asian seabass by €0.29 per tail from the default value. An increase in pellet price per kg by €1.38 and feed conversion ratio pellet by 0.96, will consequently increase the cost of grow-out Asian seabass by €2.29 per tail and €0.82 per tail, respectively. We find that the occurrence of Vibrio spp. infection at the hatchery level can contribute to an increased risk in the mortality of Asian seabass during the grow-out phase. Hence, we also need to focus on the control and prevention of vibriosis infection from hatcheries.